Satisfaction of Online Learning among Nursing Students during COVID-19 Pandemic in Pokhara - Rana, Man Maya; Shrestha, Sandhya (Journal of Lumbini Medical College, 2021)
Introduction: The outbreak of COVID-19 pandemic across the world has profoundly altered almost all aspects of life, including education. Conducting online learning was necessary to continue academic activities across all schools worldwide. The objective of this study was to assess satisfaction of online learning among nursing students. Methods: A descriptive cross-sectional study was carried out among 191 nursing students of PCL and B.Sc nursing programme. An enumerative sampling technique was used to select the sample. The self-administered web based questionnaire was used to collect data. The collected data was analysed by using descriptive and inferential statistics. Results: More than half (56%) of students were satisfied with online learning. A majority (95.8%) agreed that they need to be updated with the latest technology, 93.2% agreed on self-discipline is necessary during online class, 78% students agreed that they feel practical/clinical simulation exercises through online class is difficult, and 73.3% agreed the instructors organization and preparation for class provides comfortable online learning environment. However, only 23.56% of them agreed that they feel lazy and disinterested during online classes. There was significant association between level of satisfaction and type of residence, monthly family income, and academic level. Conclusion: More than half students are satisfied in online learning. Students’ satisfaction is one of important factors for effective outcome from online learning. So, E-learning is a good opportunity to continue education in future.